Neoliberal dirt: homelessness, stigma, and social services In Fort Collins, Colorado - Berganini, Stefanie, author; Browne, Katherine, advisor; Snodgrass, Jeff, committee member; Stevis, Dimitris, committee member (Colorado State University. Libraries, 2019)
This thesis presents a thorough investigation of the network of resources available to people experiencing homelessness in Fort Collins, Colorado. It also explores the stigma faced by the homeless community, and the ways in which stigma affects services, public policy, and the everyday lived experiences of homeless people. By exploring the various programs provided by government, non-profit, and private organizations and institutions, I aim to create a conceptual map of the sources of support available to the homeless population of Fort Collins. In doing so, I analyze both the strengths and weaknesses of the existing service network, and explore the ramifications of systemic gaps on the lives of homeless people. Using data gathered through participant observation in various resource-providing organizations, as well as via interviews with non-profit executives, city administrators, homeless advocates, faith community leaders, business community representatives, and people experiencing homelessness, I attempt to present an emic, or insider, view of the complex issues surrounding homelessness in Fort Collins. The results of this research provide actionable information that may be used to shape public policy or other programming decisions for the local community. Both housed and unhoused residents in Fort Collins can benefit from an understanding of how the network of support services functions, how stigma affects the public's view of homeless people, and how stigma and services interact. In Chapter 2, I first outline national-level data surrounding the occurrence and causes of homelessness. Next, I explore the formation of stigma, and the process of symbolic boundary-making that defines our everyday perception of the world. I then provide an overview of the ways in which governance reconfigures conceptualizations of public space, with related ramifications for homeless people existing in the public sphere. Finally, I explore existing data about homelessness in Fort Collins, and chronicle the city's recent history of homeless-related governance. Chapter 3 describes the data collection and data analysis methodologies used to generate my findings. I outline the timeline for this research, provide descriptions of my interview groups and participant observation activities, and explain the social networking process used to generate the included service network map. I also explain the transformational research framework I use to situate this work. Using a critical political economy lens, Chapter 4 explains my major research findings. First, I present the results of my network mapping process. Next, I provide an overview of the strengths in the city's existing social service network. Then, I explore the stigmatization of homeless people in Fort Collins, and the negative stereotypes held by actors in both the general public and in significant positions of power. Finally, I detail the weaknesses in the city's current attempts to deal with homelessness – including a lack of affordable housing, a failure to provide for some basic needs, a severe dearth of mental health and substance abuse services, and a policing model that sometimes makes homelessness worse, not better – and how those weaknesses affect, and are affected by, the stigmatization of homeless people. Chapter 5 synthesizes the preceding chapters and offers final conclusions about the state of homelessness in Fort Collins. It also posits actionable next steps, and suggests other relevant lines of research not covered by this paper.
Keywords: homelessness; public policy; stigma; neoliberalism; critical political economy; social services